Plankton study of Siddheshwar dam of Hingoli district, (M.S.) India. - D, Dhimdhime S; V, Waghmare N; D, Shinde V; E, Ambore N (International Multidisciplinary Research Journal, 2012)
The present paper deals with the plankton diversity of siddheshwar dam near Aundha dist Hingoli Maharashtra in the year 2001.The water spread area of the dam 40.58 Sq.Km.at FRL 250.85 Mcum. The phytoplankton represented by chlorophyceae, bascillariophyceae, cyanophyceae, and euglenophyceae and zooplankton represents species of rotifer, copepods, cladocera and ostracoda.